Na+/K+-ATPase level and products of lipid peroxidation in live cells treated with therapeutic lithium for different periods in time (1, 7, and 28 days); studies of Jurkat and HEK293 cells - Vosahlikova, Miroslava; Roubalova, Lenka; Ujcikova, Hana; Hlouskova, Martina; Musil, Stanislav; Alda, Martin; Svoboda, Petr (Naunyn-Schmiedeberg's archives of pharmacology, 2019)
Regulation of Na+/K+-ATPase in bipolar disorder and lithium therapy has been investigated for more than 40 years. Contradictory results in this area may be caused by the difference between acute and long-term Li effects on cell metabolism and variance in responsiveness of different cell types. We compared the time-course of Li action focusing on Na+/K+-ATPase and lipid peroxidation in two widely different cell models-Jurkat and HEK293. Na+/K+-ATPase expression level was determined in cells cultivated in the absence or presence of 1 mM Li for different time spans (1, 7, and 28 days) using [3H] ouabain binding and immunoblot assay of α-subunit. In parallel samples, the formation of malondialdehyde (MDA) was quantified by HPLC, and 4-hydroxy-2-nonenal (4-HNE) protein adducts were determined by immunoblot. Cultivation of Jurkat cells in 1 mM Li medium resulted in downregulation of Na+/K+-ATPase (decrease of [3H] ouabain-biding sites and intensity of immunoblot signals) in all Li-groups. In HEK293 cells, the decrease of Na+/K+-ATPase was observed after the acute, 1-day exposure only. The long-term treatment with Li resulted in Na+/K+-ATPase upregulation. MDA and 4-HNE modified proteins were decreased in Jurkat cells in all Li-groups. On the other hand, in HEK293 cells, MDA concentration was decreased after the acute, 1-day Li exposure only; the long-term cultivations, for 7 or 28 days, resulted in a significant increase of lipid peroxidation products. The Li-induced decrease of lipid peroxidation products was associated with the decrease of Na+/K+-ATPase level and vice versa.
Keywords: Jurkat Cells; Gene Expression Regulation; sodíko-draslíková ATPasa; Lithium Compounds; HEK293 buňky; Jurkat cells; Jurkat buňky; Lipid Peroxides; vztah mezi dávkou a účinkem léčiva; HEK293 Cells; sloučeniny lithia; Lithium; Lipid peroxidation products; Time Factors; lipidové peroxidy; Na+/K+-ATPase; lidé; Sodium-Potassium-Exchanging ATPase; Humans; HEK293 cells; regulace genové exprese; časové faktory; peroxidace lipidů; Lipid Peroxidation; Dose-Response Relationship, Drug; bipolární porucha; Bipolar Disorder